ナンキョク ショウワ キチ シュウヘン ノ ドジョウ コキュウ 1 ドジョウ コキュウ ソクド ト ドジョウ ノ ガンスイリツ チッソ ガンユウリョウ トノ カンケイ - 伊野, 良夫; イノ, ヨシオ; 大島, 康行; オオシマ, ヤスユキ; 神田, 啓史; カンダ, ヒロシ; 松田, 達郎; マツダ, タツロウ; INO, Yoshio; OSHIMA, Yasuyuki; KANDA, Hiroshi; MATSUDA, Tatsuro (1980)
P(論文) 1978年1月と2月に南極の昭和基地周辺各地で表層土壌を採取し,凍結状態で日本に持ち帰った.その一部72点を用いて,10℃,暗所で放出されるC0_2量を赤外線ガス分析機で測定した.土壌の湿重と乾重とから水分含有率を求めた.また,ケールダール法によってチッソを定量した.CO_2放出速度は平均13.3mgC/(kg乾燥土壌・日)で,最低値は0.0,最高値は84.9であった.東京近郊数カ所の土壌で得られた値より大きなものがいくつもあった.砂質土壌のため,水分含有率は一般に小さかった.チッソ含有率は0.001-0.45%で,きわめて小さかった.土壌呼吸速度と水分含有率,あるいはチッソ含有率との間に高い相関関係が認められた. With 72 samples of soil which were taken in the vicinity of Syowa Station, Antarctica, carbon dioxide evolution rate, i. e. soil respiration, water content and nitrogen content were measured. The range of soil respiration rates at 10℃ was 0.0 to 84.9 mg C/(kg dry soil・day). Some of soil respiration rates measured at 10℃ were higher than those taken under the same condition with a few types of floral zone in Japan. Nitrogen contents in sample soil were very low with the range of 0.011 to 4.51 mg N/g dry soil. There were good correlations between soil respiration rates and nitrogen contents or water contents. departmental bulletin paper